Nilai-nilai Pendidikan dalam Novel Sepatu Dahlan Karya Khrisna Pabichara - Mashita, Mutia; Gani, Erizal; Nst., Bakhtaruddin (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2013)
The purpose of this studyis to describe and analyze the values ​​of education contained in the novel of Khrisna Pabichara, Sepatu Dahlan, include: (1)hard work, (2) compassion, (3) discipline, (4) patient, (5) sportsmanship and its implicationsin learning Indonesia Language. The data is novel elements that reveal aspects of values ​​education, character education. The research method is descriptive qualitative. The found ofthe study is the values ​​contained in then ovelis the value ofcharacter education, which includes:(1) 10 data on hard work, (2) 12 data about affection, (3) 10 data on discipline, (4) 8 data about thepatient, (5) 2 data on sportsmanship. The results ofthe study entitled "Values ​​Educationin the Novel Sepatu Dahlan Khrisna Pabichara work and its implications in learning Indonesia Language" can be used for learning in class XI semester I of high school, on reading—aspect, SK (7), KD(2).